Human Serum Eye Drops in Eye Alterations: An Insight and a Critical Analysis - Maria Rosaria De Pascale; Michele Lanza; Linda Sommese; Claudio Napoli (Journal of Ophthalmology)
Human serum contains a physiological plethora of bioactive elements naturally released by activated platelets which might have a significant effect on the regeneration of corneal layers by stimulating the cell growth. This mechanism supported the use of human serum eye drops in some ocular diseases associated with dystrophic changes and alterations of the tear film, such as persistent corneal epithelial defects and dry eye syndrome. We focused our effort on potential benefits and limitations of the use of human serum eye drops when conventional therapies failed. We reviewed the recent literature by reporting published studies from 2010 to 2014. Despite the limited evaluated study populations, most of the clinical studies have confirmed that serum eye drop therapy is effective in corneal healing by reducing ocular symptom, particularly during the short-term follow-up. In addition, three recent published studies have shown the efficacy of the serum eye drop therapy in comparison to traditional ones in intractable patients. Besides, reported ongoing clinical studies confirmed the open debate regarding the use of biologic tools for cornea regeneration. Results from these studies might open novel challenges and perspectives in the therapy of such refractory patients.